THE IMPLEMENTATION OF CURRICULUM 2013 IN EXPEREMENT OF OPTIC COURSE THROUGH THE DEVELOPMENT OF STUDENT WORKSHEETTO ESTABLISH SCIENTIFIC ATTITUDE IN PHYSICS EDUCATION PROGRAM - Nor, Muhammad (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This study is about the Development of StudentWorksheetin Optical course which is develop scientific attitudes through learning. The Scientific which is expected through Student Worksheeton learning is; curiosity responsibility, free thinking, honesty and discipline. Through this research of development, the result in this research that Worksheet are worth to be conducted in learning process to establish the scientific attitudes in Optical course particularly for Physics Education Study Program. Keywords; Student activity sheets, educational scientific attitude